Estimation of the traction power of agricultural tractors from dynamometric tests - Russini,Alexandre (2018)
ABSTRACT: The objective of this research was to predict, from dynamometric tests, the traction performance of agricultural tractors, without the need to employ the standard official tests carried out on concrete tracks. The evaluations were conducted at the experimental area of the Universidade Federal de Santa Maria, where an instrumented agricultural tractor was subjected to dynamic field traction tests and static tests in the laboratory, using an eddy currents dynamometer. It can be verified through the correlation analysis between the values obtained and the estimated values that, based on the prediction equations, a high correlation (r² = 0.99) was obtained between the power observed in the field and the estimated power obtained using dynamometric tests. Based on the analysis of the results obtained in this study, it can be stated that the traction performance of an agricultural tractor can be estimated from dynamometric tests. We concluded that the dynamic field tests can be replaced by static tests carried out in laboratories, which are generally less expensive.